Evaluation of Novaluron 0.2 G against Aedes (Stegomyia) aegypti (Diptera: Culicidae) in an urban area in Antioquia, Colombia - Quimbayo F., Marcela; Amaya, Juan D.; Rúa-Uribe, Guillermo L. (Revista Colombiana de Entomología, 2022)
Dengue, zika and chikungunya are globally important arboviruses. In the absence of a vaccine, health entities focus mainly on vector control using insecticides, Growth Regulatory Insecticides (IRC), including Novaluron, have proven to be effective in vector control. The objective was to determine the optimal application dose of Novaluron 0.2G on the emergence of Aedes aegypti in an urban area endemic for dengue, Carepa, in the department of Antioquia, Colombia. Twenty-one dwellings were randomly selected, where three 250-L tanks were located, two corresponded to treatments and one to control, evaluating three concentrations (treatments), ramdomly selected for each dwelling. The study was carried out for 18 weeks: seven weeks of pre-treatment, one week of product application and ten weeks of post-treatment. For this, the pupae of A. aegypti were collected, allowing the emergence of adult mosquito under controlled conditions, in order to estimate the weekly inhibition of the emergence. The results indicated that a reduction in the emergence of A. aegypti of close to 100% was achievedwith the highest concentration evaluated (0.584 mg/L). For the other concentrations (0.292 and 0.146 mg/L), the percent inhibition of emergence for week two was 79% and 45%, respectively.